Breathless in the bath. Issue 6 (23rd May 2006) - Whyte, G P; Harries, M; Dickinson, J; Polkey, M I
Abstract : The case is reported of a male track and field athlete with breathing difficulties at rest and during exercise, which were exacerbated in the supine position and during water immersion. Right hemidiaphragmatic paralysis was diagnosed. The cause of this relatively benign disorder is not known and there are no serious clinical implications. There is no treatment, but a continuation of exercise together with interventions to strengthen the subsidiary inspiratory muscles is recommended.